A high-performance electrocatalyst via graphitic carbon nitride nanosheet-decorated bimetallic phosphide for alkaline water electrolysis - Kayis, Zehra; Akyuz, Duygu (Royal Soc Chemistry, 2024)
Developing renewable and clean energy systems for overall water electrolysis requires low-cost, highly efficient, and stable catalysts. With this motivation, nickel cobalt phosphorus (NiCoP) was electrodeposited onto nickel foam (NF) and then modified with graphitic carbon nitride (g-C3N4). The designed g-C3N4/NiCoP/NF electrode was used for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in alkaline water electrolysis. It exhibited a small overpotential of 80 mV@10 mA cm(-2) with a Tafel slope of 89 mV dec(-1) for the HER. It also exhibited an overpotential of 370 mV@10 mA cm(-2) with a Tafel slope of 64 mV dec(-1) for the OER. The g-C3N4/NiCoP catalyst exhibited satisfactory stability in an alkaline electrolyzer system, in which g-C3N4/NiCoP/NF was used as the anode and cathode. Meanwhile, the electrocatalyst requires only a cell voltage of 1.70 V to achieve 10 mA cm(-2) current density for overall water electrolysis.
Keywords: Hydrogen Evolution Reaction; Reduced Graphene Oxide; Bifunctional Electrocatalyst; Oxygen Reduction; Efficient; Arrays; Nicop; Photocatalyst; Nicop/G-C3n4; G-C3n4